Direct laser writing of high-Q polymeric microresonators for Photonics - Tomazio, Nathália Beretta (2020)
Optical microresonators have been driving considerable advances in science due to their ability to strongly confine light within small dielectric volumes and their unique features, such as frequency selectivity, high sensitivity and ease of integration into a range of photonic systems. In particular, polymers are attractive as a resonator material owing to their structural flexibility, ease of processing/functionalization and low cost. However, the fabrication of high quality factor polymeric microresonators by means of simple fabrication methodologies that afford fine tuning of the structure dimensions and its integration into different platforms/substrates is still on great demand. In this work, we demonstrated the potential of femtosecond laser writing via two-photon polymerization to fabricate high quality factor polymeric whispering gallery mode microresonators, which were doped with active compounds aiming at photonic applications. Our microresonators were fabricated from an acrylic-based photoresist. They are 50 μm diameter hollow microcylinders featuring sidewall roughness of 1.5 nm, which makes them suitable for photonic applications at visible and infrared wavelengths. They exhibit a quality factor of 1×105 at 1550 nm, a high performance achieved in a single step of femtosecond laser writing. In order to enable laser operation, we doped the microresonators with rhodamine B. The great power enhancement achieved within the microresonators, combined with the high fluorescence quantum yield of rhodamine B, allows for a lasing threshold as low as 12 nJ for free space picosecond excitation at 532 nm. Moreover, we investigated the mechanisms underlying a mode cleaning effect in microresonators to which we had incorporated graphene oxide. By calculating the resonances response to damping mechanisms in the microresonators, we showed that additional losses introduced by graphene oxide play a major role in reducing the visibility of a number of resonances up to the point of effectively filtering a set of modes out. Overall, this work provides a simple strategy to accomplish high quality factor polymeric microresonators and offers interesting physical insights that can be useful in the design and fabrication of photonic micro/nanodevices.